Tradisi Wuku Taun sebagai Bentuk Integrasi Agama Islam dengan Budaya Sundah pada Masyarakat Adat Cikondang - Deni Miharja (UIN Maulana Malik Ibrahim Malang, 2013)
This article write starts from some phenomena of the relation between religions and local cultures. Such relation is interesting to do research that interpretations of the relation between religion and local cultures to certain societies are various. The interaction between Islam and local cultures also undergoes variuos form of relation. Variety of the form of relation between Islam and local cultures in a society depends upon their understanding and interpretation of Islamic teachings itself. One of the forms of relation between Islam and local cultures can be found in traditional society of Cikondang. The form of relation between Islam and local cultures was occurred in traditional society in Cikondang tends to be the form of integration wich certain pattern. Therefore, the focus of this writer article is to describe relation between Islam and Sundanese cultures in form of integration with wuku taun. Based on data of research the tradisional society of Cikondang represents the part of Sundanese society in wich all of them are muslims. This goes hand in hand with the statement that Islam is Sunda and Sunda is Islam. Sundanese people are Muslims before Islam comes to Sundanese society. Artikel ini berangkat dari fenomena hubungan agama dengan budaya lokal. Dimana hubungan agama dengan budaya lokal pada suatu masyarakat, mengalami bentuk hubungan yang beragam. Begitu pun hubungan agama Islam dengan budaya lokal mengalami bentuk hubungan yang beragam pula. Beragamnya bentuk hubungan agama Islam dengan budaya lokal pada suatu masyarakat tergantung dari penghayatan terhadap ajaran Islam itu sendiri. Bentuk hubungan agama Islam dengan budaya lokal bisa ditemukan salah satunya pada masyarakat adat Cikondang. Bentuk hubungan yang terjadi antara Islam dengan budaya Sunda pada masyarakat adat Cikondang cenderung dalam bentuk integrasi dengan pola tertentu, sehingga fokus penulisan artikel ini adalah untuk mengungkap hubungan agama Islam dengan budaya Sunda dalam bentuk integrasi melalui tradisi wuku taun. Berdasarkan data yang diperoleh, masyarakat Cikondang merepresentasikan sebagian masyarakat Sunda yang seluruhnya beragama Islam. Hal ini tentu sejalan dengan beberapa pernyataan yang menyebutkan Islam itu Sunda dan Sunda itu Islam, orang Sunda sudah Islam sebelum Islam